Ruptured Sinus of Valsalva Aneurysm: Use of Multimodality Imaging in Delineating Structure and Function. (May 2021) - Kassab, Kameel; Kaul, Subuhi; Gomez, Javier; Delafontaine, Jean-Luc; Sawaqed, Ray; Saini, Abhimanyu
Sinus of Valsalva aneurysm is a rare defect that can present with fatal complications in case of rupture. Heart failure symptoms are common due to high fraction of the resultant shunt. Multimodality imaging and invasive hemodynamic assessment is essential for comprehensive evaluation of the defect and guiding surgical planning. We describe the case of a 40-year-old woman who presented with heart failure symptoms and was found to have ruptured sinus of Valsalva aneurysm on transthoracic echocardiogram. Cardiac computed tomography angiography further characterized the defect and the associated anomalies. Right heart catheterization assessed the hemodynamic significance of the left to right shunt. Intraoperative findings highlighted the associated congenital anomalies including supracristal ventricular septal defect. The use of intraoperative transesophageal echocardiography proved essential in detecting worsening of the right ventricular outflow track infundibular dynamic obstruction post repair thus delineating the importance of maintaining adequate cardiac preload. This case highlights a stepwise approach in the anatomical characterization of sinus of Valsalva aneurysm using multimodality imaging and the use of hemodynamic assessment and intraoperative imaging to guide surgical planning.